An overview of the research on the correlation between solar energy utilization potential and spatial morphology - Dexin Li; Xiurong Cui; Ligang Shi; Yuan Li (Results in Engineering)
The combination of solar energy utilization and spatial morphology is crucial to improve urban energy efficiency. This paper explores the internal relationship between solar energy potential assessment and spatial form indicators from three aspects: research progress related to solar energy utilization potential, its correlation with spatial form indicators, and spatial form optimization methods and frameworks. According to the corresponding categories of different indicators, the research conclusions and effectiveness are summarized from three aspects: overall planning, group layout and architectural form, aiming to provide theoretical reference for urban sustainable development. The review shows that most of the studies in this field mainly employ geometric and descriptive morphological parameters to indirectly reflect the neighborhood relationship of buildings, while more complex multi-dimensional parameters or performance parameters characterizing building properties remain to be explored. In addition, it is necessary to build a sound comprehensive benefit evaluation system that integrates product information related to solar energy system and physical information related to building environment; in the meantime, advanced simulation technology and big data analysis will be introduced to improve the rational distribution and utilization efficiency of solar light heat among building groups.